The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/0844562118821573
|View full text |Cite
|
Sign up to set email alerts
|

“Mutual Respect Would be a Good Starting Point:” Students’ Perspectives on Incivility in Nursing Education

Abstract: Background Studies indicate that incivility is common in nursing education and perpetuated by both students and faculty. Academic incivility negatively affects the well-being of those involved, interferes with the teaching–learning process, and is antithetical to nursing as a caring profession. An understanding of academic incivility is essential to establish best practices to address this problem. Purpose The purpose of this study was to examine incivility in nursing academia from the perspective of baccalaur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 35 publications
(141 reference statements)
0
20
0
Order By: Relevance
“…Students, faculty members, and health professionals are professionally required to commit themselves to building respectful and appropriate learning/working environments that promote effective communication and collaboration [ 45 ]. Learning about mutual respect in cyberspace is a good starting point for addressing incivility and establishing a safe and supportive learning environment [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Students, faculty members, and health professionals are professionally required to commit themselves to building respectful and appropriate learning/working environments that promote effective communication and collaboration [ 45 ]. Learning about mutual respect in cyberspace is a good starting point for addressing incivility and establishing a safe and supportive learning environment [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has come to light that not only is experiencing bullying an issue but witnessing it is also problematic (Báez-León et al, 2016;MacCurtain et al, 2018). While in this paper we focus on the experience of students, it is important to note that nursing faculty may also experience bullying or incivility (Gazza, 2009;Small et al, 2019).…”
Section: The Magnitude and Impact Of Bullying In Practice And Educationmentioning
confidence: 99%
“…As an example, 89% of surveyed nursing students in a Canadian school of nursing reported experiencing bullying (Clarke et al, 2012). A 2019 study of Canadian nursing students likewise found that 87% felt that "incivility" in nursing education was a problem (Small et al, 2019). Bishop (2004) conducted a qualitative analysis of the experiences of practising nurses while Hunt and Marini (2012) looked specifically at the experiences of clinical instructors.…”
Section: The Magnitude and Impact Of Bullying In Practice And Educationmentioning
confidence: 99%
“…Several scholars concur that bullying begins during undergraduate nursing education and continues to thrive in nursing practice. [6,9,[11][12][13][14] Undergraduate nursing students are expected to complete a minimum amount of clinical practice hours as part of their undergraduate nursing program. For example, in Australia, nursing students must undertake a minimum of 800 clinical placement hours in their undergraduate nursing program.…”
Section: Introductionmentioning
confidence: 99%